Investigation of urban ethnoveterinary in three veterinary clinics at east zone of São Paulo city, Brazil. (15th September 2015) - Antonio, RL; Souza, RM; Furlan, MR; Pedro, CR; Cassas, F; Honda, S; Rodrigues, E
Abstract: Ethnopharmacological relevance: Urban Ethnoveterinary should be further explored because of its value as it resists conventional medical care. In addition, the comparison between the resources used by Ethnoveterinary and Ethnopharmacology should be investigated in depth, increasing the availability of new bioactive potential in human and veterinary medicines. This project aimed to determine whether plants are used in the health care of dogs and/or cats in urban area and to compare its uses with other ethnoveterinary and ethnopharmacological data. Materials and methods: Three veterinary clinics from east area of São Paulo city were selected, in order to record the offering of plants to pets by their owners. Individual interviews were conducted from May to November 2012 and consisted of application of semi-structured interviews and questionnaires. A literature search was performed to compare our findings with other ethnopharmacological and ethnoveterinarian data from the literature. Results: A total of 273 people were interviewed and 46 (16.84%) of them utilize medicinal plants for their pets. Most plant species are exclusively home grown (57.9%). The plants most cited were Plectranthus barbatus Andrews, Matricaria chamomilla L. and Foeniculum vulgare Mill. The most frequent route of administration, part utilized and mode of preparation was oral (80.35%), leaves (89.47%) and infusion (61.90%), respectively. From 19 cited plants, 14 (73.7%) are mentioned in ethnoveterinary literature, whereas 11 (57.9%) are used for the same purposes. All plants reported in our study have at least one common use with ethnopharmacology. Conclusion: The survey provided evidence of ethnoveterinary use of medicinal plants for dogs and/or cats in urban area of São Paulo, complementarily with the official veterinary, and showed that the plants used in pets are also used in humans with the same purposes and routes of administration, as well as in other animals. Graphical abstract: